Delineating the switch between senescence and apoptosis in cervical cancer cells under ciclopirox treatment - Herrmann, Anja; Kuhn, Bianca; Holzer, Angela; Krijgsveld, Jeroen; Hoppe-Seyler, Karin; Hoppe-Seyler, Felix (Cancers, 2022)
The iron-chelating drug ciclopirox (CPX) may possess therapeutic potential for cancer treatment, including cervical cancer. As is observed for other chemotherapeutic drugs, CPX can induce senescence or apoptosis in cervical cancer cells which could differently affect their therapy response. The present study aims to gain insights into the determinants which govern the switch between senescence and apoptosis in cervical cancer cells. We performed proteome analyses, proliferation studies by live-cell imaging and colony formation assays, senescence and apoptosis assays, and combination treatments of CPX with inhibitors of oxidative phosphorylation (OXPHOS) or glycolysis. We found that CPX downregulates OXPHOS factors and facilitates the induction of apoptosis under limited glucose availability, an effect which is shared by classical OXPHOS inhibitors. Under increased glucose availability, however, CPX-induced apoptosis is prevented and senescence is induced, an activity which is not exerted by classical OXPHOS inhibitors, but by other iron chelators. Moreover, we show that the combination of CPX with glycolysis inhibitors blocks cervical cancer proliferation in a synergistic manner. Collectively, our results reveal that the phenotypic response of cervical cancer cells towards CPX is strongly dependent on glucose availability, link the pro-apoptotic and pro-senescent activities of CPX to its bifunctionality as an OXPHOS inhibitor and iron chelator, respectively, and provide a rationale for combining CPX with glycolysis inhibitors.